Fetal volvulus without malrotation due to a congenital mesenteric defect presenting as fetal arrythmia: A singular case report - Francesca Nascimben; Pierre Kuhn; Nicolas Sananes; Isabelle Talon (Elsevier, 2023)
Introduction: Congenital volvulus without a prenatal diagnosis of malrotation is an extremely rare cause of acute intestinal obstruction in the foetal and neonatal period with a high morbidity and mortality. The aim of this report is to describe prenatal imaging, pregnancy characteristics and clinical outcomes to identify a gold standard management approach for neonates affected by congenital volvulus through our experience with this case as well as a review of the literature. Case presentation: We describe an intrauterine case of volvulus without malrotation suspected by prenatal ultrasound at 28 weeks' gestation, with enlarged hyperechogenic loops without peristalsis in a 715g preterm boy born at 29 weeks' gestation. The discrepancy between the minimal clinical manifestations and the severity of intestinal pathology is highlighted. At explorative laparotomy following delivery, a congenital mesenteric defect was identified through which small bowel had herniated and volvulised, causing prenatal bowel dilatation and necrosis. The necrotic bowel was resected, and both an ileostomy and jejunostomy were created within 30 hours of birth. However, severe post-operative complications were encountered, which ultimately led to the newborn's death. Conclusion: Foetal volvulus is a rare condition with high rates of preterm birth and perinatal mortality. A high index of suspicion is required in cases of bowel dilatation, intestinal duplication or malrotation. Strict foetal follow up with serial ultrasound assessment and planned cesarean delivery are recommended. Multidisciplinary care is essential. Time of delivery and surgical intervention should be standardised to reduce the risk of neonatal mortality.